2018
DOI: 10.29252/johe.7.2.103
|View full text |Cite
|
Sign up to set email alerts
|

The association between health literacy and self-medication behaviors among women referred to comprehensive health care centers in Sirjan, Iran, in 2017

Abstract: Article Info Background: Self-medication is a challenging issue in health care systems and it seems that health literacy is a determining factor in safe self-medication behaviors. Limited studies are available in this field. Therefore, the aim of this study was to determine the relationship between health literacy and self-medicating behaviors among women referred to comprehensive health care centers Materials and Methods: In this descriptive study, 540 women, who were referred to comprehensive health care cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…According to the results, health literacy as one of the important factors in promoting community health has a significant relationship with self-medication behavior, but in the study population, this relationship was negligible contrary to expectations. The findings of this study confirmed those of some studies on the relationship between health literacy and self-medication, including Javadzade et al ( 16), Muflih et al (25), and Kamran et al (24); however, the results of the current study do not match the findings of Mousaeipour et al (23). In explaining this result, it can be stated that health literacy as a valuable asset by increasing cognitive skills (20), as well as skills needed for the integration of health information, direction, processing, problem-solving, and decision-making (21), enables people to carefully evaluate health-associated issues before any action, and all of their aspects and effects, thus individuals make decisions about self-medication with greater sensitivity.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…According to the results, health literacy as one of the important factors in promoting community health has a significant relationship with self-medication behavior, but in the study population, this relationship was negligible contrary to expectations. The findings of this study confirmed those of some studies on the relationship between health literacy and self-medication, including Javadzade et al ( 16), Muflih et al (25), and Kamran et al (24); however, the results of the current study do not match the findings of Mousaeipour et al (23). In explaining this result, it can be stated that health literacy as a valuable asset by increasing cognitive skills (20), as well as skills needed for the integration of health information, direction, processing, problem-solving, and decision-making (21), enables people to carefully evaluate health-associated issues before any action, and all of their aspects and effects, thus individuals make decisions about self-medication with greater sensitivity.…”
Section: Discussionsupporting
confidence: 53%
“…Given the concept of self-medication and its harms, as well as the concept and positive consequences of health literacy, it is expected that there is a relationship between the level of health literacy and self-medication because insufficient health literacy is associated with declining health in society (23). However, the results of studies on the relationship between health literacy and self-medication show conflicting results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the findings of the current study do not correspond to those of other studies, which revealed that patients who self-medicate also demonstrated greater levels of health literacy [ 81 ]. The discrepancy could be due to other variables, such as poverty, the fact that the participants in Mousaeipour et al’s [ 82 ] study were women and legislation governing the trade and use of drugs. Self-medication practices can develop in different countries with varying patterns, given that most human behaviors are influenced by ideas, ideologies and conventions depending on the cultural and social environment of the area [ 83 ].…”
Section: Discussionmentioning
confidence: 99%